2023
DOI: 10.3390/brainsci13040530
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Comparison of Drug-Resistant Trigeminal Neuralgia Surgical Treatments—An Umbrella Review of Meta-Analyses and Systematic Reviews

Abstract: Medical treatment for trigeminal neuralgia (TN) is not always a feasible option due to a lack of full response or adverse effects. Open surgery or percutaneous procedures are advocated in these cases. Several articles have compared the results among different techniques. Nevertheless, the findings of these studies are heterogeneous. Umbrella reviews are studies sitting at the peak of the evidence pyramid. With this umbrella review, we provided a systematic review of the outcomes of the surgical procedures used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…It is often indicated in patients with diagnosed neurovascular conflict, but it is recommended for patients who can withstand open neurosurgical procedures. Other treatments include "endoscope-assisted microvascular decompression," "percutaneous balloon decompression," and "percutaneous glycerol injection," and "extracranial peripheral denervation" [ 11 ]. Radiosurgery procedures mainly "gamma knife radiosurgery" and "radiofrequency rhizotomy" are among the recent advances where the fields of radiology and neurosurgery are merged to form a minimally invasive form of surgical treatment modality [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is often indicated in patients with diagnosed neurovascular conflict, but it is recommended for patients who can withstand open neurosurgical procedures. Other treatments include "endoscope-assisted microvascular decompression," "percutaneous balloon decompression," and "percutaneous glycerol injection," and "extracranial peripheral denervation" [ 11 ]. Radiosurgery procedures mainly "gamma knife radiosurgery" and "radiofrequency rhizotomy" are among the recent advances where the fields of radiology and neurosurgery are merged to form a minimally invasive form of surgical treatment modality [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trigeminal neuralgia (TN) is an infrequent condition manifested by excruciating unilateral electric shock-like facial pain, with classical abrupt onset and termination [1][2][3][4][5][6][7][8] . TN may be idiopathic, but the etiological factors include vascular nerve compression (classic TN), multiple sclerosis, tumor, trauma, herpes zoster, and temporomandibular dysfunction (secondary TN); arterial hypertension and diabetes are comorbidities 1,2,5,8 . The pains may start by eating, drinking, talking, touching the face, or a puff of wind 2 .…”
Section: Dear Editormentioning
confidence: 99%
“…The intensity and persistence of painful episodes cause deleterious effects on the work activities and quality of life of the patients, mainly those presenting refractory pain [1][2][3][4][5] . Consistent literature data have confirmed the high efficacy and tolerability of utilizing gabapentin and other α2δ ligands to control patients with this excruciating pain, carbamazepine and oxcarbazepine are also recommended to first-line pharmacotherapy; additional procedures can include nerve blocks, surgery, or radiofrequency ablation [1][2][3][4][5][6][7][8] . Alvarado Bardales, et al reviewed the findings of 61 patients with TN in Mexico during the year of 2019; 62.3% were females, the mean age was 60.2 ± 16.8 years, the involved sites were left branch combinations (36.1%), right branch (27.9%), and right maxillary branch (13.1%) 1 .…”
Section: Dear Editormentioning
confidence: 99%
“…6 The management of this condition requires a patient-tailored approach, although the surgeon's experience or the patient's preference are often still decisive in the selection of a surgical option. 23 A telling example in this regard is the surgical treatment of MS-TN. Montano et al 22 reported that MVD often remains an option for MS-TN despite the absence of clear indications for this procedure in such patients.…”
Section: Controversies Regarding the Selection Of A Surgical Approach...mentioning
confidence: 99%